MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA - Dwi Agustini (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2019)
This reseach purposes to increase the activity and the study result of sains student in VIII classin two semester in SMPN 19 Mataram by the sub discussion the respiratory system human. This reseach is a class action reseach which purposes to: (1) increase the sains study activity; (2) increase the sains result. The reseach is the class action reseach which is conductedin there circles, each circle consists of four steps, such as the planning, action, observation, and reflection. The results showed that in the third cycle, the average student learning outcomes rose to 74.05, with the number of students who finished studying as much as 77.23% of 22 students. This shows that the completeness of classical study in class VIII has been reached, because of completeness of classical study achieved when 75% had obtained a value of ≥ 72. Based on the research result, it can be concluded that cooperative learning model of Team Game Tournament (TGT) can increase the activity and learning result of sains of VIII class students SMPN 19 Mataram academic year 2018/2019.